Distance learning in medicine / Učenje medicine na daljavo? - Pahor, Dušica (Acta Medico-Biotechnica, 2021)
In March, an epidemic of coronavirus was announced, and a state of emergency was declared. The introduced measures have, among other things, halted in-person pedagogy in schools and faculties, having been replaced by distance learning. Furthermore, the University Clinical Centre and the Faculty of Medicine of the University of Maribor were closed to medical students ...
Keywords: University of Maribor; Faculty of Maribor; Distance learning